Edge–end collaborative secure and rapid response method for multi-flow aggregated energy dispatch service in a distribution grid - Shi, Zhan (Frontiers in Energy Research, 2024)
With a high proportion of distributed source-grid-load-storage resources penetrating into the distribution network, multi-flow aggregated energy dispatch is essential to enhance renewable energy consumption capacity and maintain grid stability. However, intelligent energy dispatch has stringent requirements for low latency and security, which necessitates the development of secure and rapid response methods. In this paper, we combine the edge-end collaboration with container microservices architecture, and propose a container and microservice empowered edge-end collaborative secure and rapid response framework for multiflow aggregated energy dispatch service in distribution grid. Then, a container selection optimization problem is formulated to minimize the total microservices execution delay. To cope with the dynamic environment such as electromagnetic interference, noise, and workload variation, we propose a microservice container selection algorithm based on enhanced ant colony with empirical SINR and delay performance awareness. The proposed algorithm benefits from the local and global integrated pheromone updating methods as well as empirical performance based dynamic pheromone and heuristic information updating mechanism. Simulation results demonstrate that the proposed algorithm outperforms existing methods in average service execution delay and convergence speed.